A new species of Astyanax (Characiformes, Characidae) from Uruguay river basin in Argentina, with remarks on hook presence in Characidae - Azpelicueta, Maria de Las M. (2000)
In the present paper the new species Astyanax ojiara n. sp. is described, from the headwaters of Yabotí river, an affluent of Uruguay river in the province of Misiones, Argentinean northeast. A combination of characters differentiates the new species from other congeners: one heptacuspid maxillary teeth; teeth of inner premaxillary row gently expanded distally; 7-9 dentary teeth decreasing in size anteroposteriorly; males with hooks in all fins; large males with pelvic axillary scale bearing 1 to 8 hooks; 36-38 perforated scales in lateral line; 20-23 branched anal-fin rays. Number of scales in the lateral line and branched anal-fin rays, humeral spot, and low body of Astyanax ojiara n. sp. resemble those of A. eigenmanniorum, but maxillary, premaxillary and dentary teeth differ in both species. The disposition of the dentary teeth is also present in A. taeniatus and A. giton but A. ojiara n. sp. has one heptacuspid maxillary tooth.